Animal Virus Pathogenesis : a Practical Approach - Oldstone, Michael B.A; Ed (Practical approach series., 1990)
The study of animal virus pathogenesis is a rapidly developing area. Understanding viral pathogenesis requires knowledge and use of techniques drawn from several disciplines by researchers working at the interface between virology and immunology. This volume charts the way that viral tropism, viral expression and viral infectivity are assayed.